The Comprehensive Cancer Center Development, Integration, and Implementation - Aljurf, Mahmoud; Majhail, Navneet S.; Koh, Mickey B.C; Kharfan-Dabaja, Mohamed A.; Chao, Nelson J. (Springer Nature, 2022)
This open access book provides a valuable resource for hospitals, institutions, and health authorities worldwide in their plans to set up and develop comprehensive cancer care centers. The development and implementation of a comprehensive cancer program allows for a systematic approach to evidence-based strategies of prevention, early detection, diagnosis, treatment, and palliation. Comprehensive cancer programs also provide a nexus for the running of clinical trials and implementation of novel cancer therapies with the overall aim of optimizing comprehensive and holistic care of cancer patients and providing them with the best opportunity to improve quality of life and overall survival. This book's self-contained chapter format aims to reinforce the critical importance of comprehensive cancer care centers while providing a practical guide for the essential components needed to achieve them, such as operational considerations, guidelines for best clinical inpatient and outpatient care, and research and quality management structures. Intended to be wide-ranging and applicable at a global level for both high and low income countries, this book is also instructive for regions with limited resources. The Comprehensive Cancer Center: Development, Integration, and Implementation is an essential resource for oncology physicians including hematologists, medical oncologists, radiation oncologists, surgical oncologists, and oncology nurses as well as hospitals, health departments, university authorities, governments and legislators.